Modifications of Recognition Memory Processes in Preterm Children: An Event‐Related Potential Study. Issue 2 (17th December 2014) - Kipp, Kerstin H.; Mecklinger, Axel; Brunnemann, Nicole; Shamdeen, Mohammed G.; Meng‐Hentschel, Juliane; Gortner, Ludwig
Abstract : Prematurity may cause hippocampal compromise. Therefore, hippocampus‐dependent memory processes (recollection‐based retrieval) may be more impaired than hippocampus‐independent processes (familiarity‐based retrieval). The memory of 18 children born preterm with reduced hippocampal volumes, without neonatal complications (weeks of gestation < 34, weight < 1, 600 g), and 15 controls (8–10 years) was tested using an item recognition task. While groups were equal in memory performance, dissociation was found: The event‐related potential (ERP) correlate of familiarity was intact in the preterm group, whereas the correlate of recollection was attenuated. A follow‐up experiment ruled out that this was due to general cognitive deficits. Furthermore, gestational age correlated with the ERP index of recollection. Thus, recognition memory in preterm children may be characterized by a compensation of attenuated recollection by familiarity.